2012
DOI: 10.1128/mcb.00293-12
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Selenocysteine Lyase-Mediated Selenium Recycling Pathway Leads to Metabolic Syndrome in Mice

Abstract: Selenium (Se) is an essential trace element used for biosynthesis of selenoproteins and is acquired either through diet or cellular recycling mechanisms. Selenocysteine lyase (Scly) is the enzyme that supplies Se for selenoprotein biosynthesis via decomposition of the amino acid selenocysteine (Sec). Knockout (KO) of Scly in a mouse affected hepatic glucose and lipid homeostasis. Mice lacking Scly and raised on an Se-adequate diet exhibit hyperinsulinemia, hyperleptinemia, glucose intolerance, and hepatic stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 65 publications
7
105
3
Order By: Relevance
“…Surprisingly, SCL knockout mice are characterized by disrupted glucose and lipid homeostasis and insulin signaling when fed a normal Se diet. Furthermore, these symptoms worsened when animals were subjected to Se deficiency leading to development of obesity and hypercholesterolemia (309). The data suggest that the metabolic perturbations caused by the lack of SCL might be due to defects in selenoprotein synthesis and are in line with the recently observed link between selenoprotein deficiency and disrupted glucose homeostasis in mice (198).…”
Section: E Sec Lyasesupporting
confidence: 68%
See 1 more Smart Citation
“…Surprisingly, SCL knockout mice are characterized by disrupted glucose and lipid homeostasis and insulin signaling when fed a normal Se diet. Furthermore, these symptoms worsened when animals were subjected to Se deficiency leading to development of obesity and hypercholesterolemia (309). The data suggest that the metabolic perturbations caused by the lack of SCL might be due to defects in selenoprotein synthesis and are in line with the recently observed link between selenoprotein deficiency and disrupted glucose homeostasis in mice (198).…”
Section: E Sec Lyasesupporting
confidence: 68%
“…Recent advances in characterizing the physiological role of SCL have been provided by whole body knockout of the SCL gene in mice (309). Surprisingly, SCL knockout mice are characterized by disrupted glucose and lipid homeostasis and insulin signaling when fed a normal Se diet.…”
Section: E Sec Lyasementioning
confidence: 99%
“…To investigate the physiological role of Scly in vivo, our laboratory previously generated Scly KO (Scly Ϫ/Ϫ ) mice. These mice exhibited mild obesity with no discernible neurological deficits when fed a standard laboratory diet (8,9). However, upon challenge with a low selenium diet, we observed cognitive deficits, reduced glutathione peroxidase activity in the brain, and the development of metabolic syndrome in these mice.…”
mentioning
confidence: 69%
“…Mice lacking Scly develop metabolic syndrome and become obese, with hyperinsulinemia, hyperleptinemia, and hypercholesteremia, which are aggravated by a selenium-deficient diet (55). These findings demonstrated that Scly plays a role in energy metabolism and raised the question of whether this role could be independent of its function in selenoprotein biosynthesis.…”
Section: Innovationmentioning
confidence: 97%